Analysis of the prevalence of polypharmacy and the pharmacotherapeutic profile of elderly people enrolled in a family health unit (Research, Society and Development, 2021)
Objective: to analyze the prevalence of polypharmacy and the pharmacotherapeutic profile of elderly people enrolled in a family health unit. Methods: Cross-sectional, quantitative, descriptive and analytical pharmacoepidemiological study, carried out with individuals aged 60 years or more in the city of Lafaiete Coutinho – BA. The association between variables was tested using Poisson Regression, with robust calculation of prevalence ratios (PR) and 95% confidence interval (95%CI) and significance p